Co-resistance to Chromium and Antibiotics in Bacteria Isolated from Tannery Wastes - Mahmud, Jalish; Chowdhury, Miraj Kobad; Sami, Abdullah Bashar; Akhand, Anwarul Azim; Ahsan, Nazmul (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Bacteria isolated from tannery wastes were evaluated for their resistance towards chromium (Cr) as well as antibiotics. Out of the twelve isolates, three bacterial strains showed Cr resistance even at 10 mg/ml concentration and were cocci in shape. Antibiogram suggested that these Cr-resistant bacteria were also resistant to multiple antibiotics. This study suggested that exposure to Cr in the environment can also lead to the development of antibiotic resistant microorganisms. Future research will disclose the mechanism underlying the existence of such dual resistance and also its impact on public health. Dhaka Univ. J. Pharm. Sci. 14(2): 193-197, 2015 (December)